USM, USC SIGN MOU TO ESTABLISH COLLABORATION IN SCIENCE AND CULTURE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 24 January 2016 Universiti Sains Malaysia (USM) continued to spread its wings across the globe with the signing of a memorandum of understanding (MoU) with Iran’s University of Science and Culture (USC).